Transformation of Public Services Policy Analysis of Digital Population Identity (IKD) in Surabaya City - Desak Gede Suasridewi; Fedianty Agustina; Sri Kamariyah; Widyawati Widyawati; Eny Haryati (International Journal of Social Science and Humanity, 2025)
This study analyzes the transformation of public services in Surabaya City through the implementation of Digital Population Identity (IKD), focusing on efficiency, effectiveness, transparency, accountability, and public participation. Using a qualitative case study method, data were collected through interviews, observations, and document analysis from policymakers, policy implementers, and the community. The findings show a positive impact of IKD on service efficiency and effectiveness, but challenges remain, particularly related to digital literacy. Transparency has improved due to real-time information access. Accountability has increased through digital complaint features, though staff capacity needs enhancement. Public participation has risen. The study recommends enhancing socialization, digital literacy, technological infrastructure, and staff capacity to maximize the benefits of IKD.